Staff and Student Views of AUTonline (BlackBoard) after Three Years - Andrew Higgins; Janneke Kreieg (Flexible Learning Association of New Zealand, 2012)
This article reports on the views of both staff and students at AUT University after having had three years' experience using the BlackBoard learning management system, locally renamed AUTonline. The university sought the assistance of its Institutional Research Unit (IRU) to conduct two surveys, one of staff opinions and one from students. There were 210 out of 400 identified regular staff users responding to the questionnaire. The IRU identified 8,000 regular student users of the system, randomly selecting 1,500 and receiving a response from 499 students. The survey found that both staff and students were about 80 percent satisfied with their experiences with the learning management system in general; no category of issues in the survey fell into the less-than-satisfactory bandwidth. No similar institutional surveys have been conducted by universities in New Zealand, so the outcomes of the survey have been located more in the Australasian context.